2022
DOI: 10.3389/fcimb.2022.983608
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microbiota of periodontitis aggravates bone loss in ovariectomized rats

Abstract: The mechanisms underlying the crosstalk between periodontitis and osteoporosis remain unclear. Recently, the gut microbiota has been recognized as a pivotal regulator of bone metabolism, and oral and gut mucosae are microbiologically connected. In this study, we investigated the effects of periodontitis on osteoporosis through the oral-gut axis. The salivary microbiota of patients with periodontitis was collected and then pumped into the intestine of Sprague–Dawley rats via intragastric administration for 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The biological safety of biomaterials in vivo , particularly with respect to their absorption, metabolization, and bioaccumulation, always remains a crucial issue. Recently, several studies have demonstrated crosstalk between the salivary and intestinal microbiota. To preliminarily evaluate the biosafety of Nell-1-combined AuNPs, the tissue morphology of important organs, the integrity of intestinal epithelium in colon, and the homeostasis of gut microbiome were assessed. H&E staining images of the key organs (lungs, kidneys, and liver) from different groups failed to reveal any abnormality as compared to the Ctrl group (Figure S4), suggesting that Nell-1-combined AuNPs did not exhibit any obvious organ toxicity in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…The biological safety of biomaterials in vivo , particularly with respect to their absorption, metabolization, and bioaccumulation, always remains a crucial issue. Recently, several studies have demonstrated crosstalk between the salivary and intestinal microbiota. To preliminarily evaluate the biosafety of Nell-1-combined AuNPs, the tissue morphology of important organs, the integrity of intestinal epithelium in colon, and the homeostasis of gut microbiome were assessed. H&E staining images of the key organs (lungs, kidneys, and liver) from different groups failed to reveal any abnormality as compared to the Ctrl group (Figure S4), suggesting that Nell-1-combined AuNPs did not exhibit any obvious organ toxicity in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Because microbial interactions between the oral cavity and gut occur frequently and the interactions may affect HTN and many other diseases ( 27 , 50 , 51 ), we analyzed communications between the oral and gut viromes. Approximately one-third of oral viruses were prevalent in the gut, and Pepyhexavirus from subgingival plaques may be transferred to the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva contains mucus (comprised of water, lipids and proteins such as mucins) which can protect microbiota from gastric acid for survival along the gastrointestinal tract [ 15 ]. Oral gavage of periodontitis-related saliva can aggravate mice models of diabetes [ 16 ], colitis [ 17 ], Alzheimer’s disease [ 18 ] and osteoporosis [ 19 ]. Patients with severe periodontitis were estimated to swallow approximately 10 12 -10 13 Porphyromonas gingivalis (P. gingivalis) bacteria per day [ 20–22 ], and oral gavage of P. gingivalis in mice could alter gut microbiota [ 23–25 ].…”
Section: Routes Of Oral Microbiota To Affect Gut Microbiotamentioning
confidence: 99%